1986
DOI: 10.1002/1097-0142(19860701)58:1<37::aid-cncr2820580108>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of bone tumors using a monoclonal antibody raised against human osteosarcoma

Abstract: The radiolabeled monoclonal antibody 791T/36 raised against a human osteosarcoma was injected into 20 patients with known or suspected bone tumors. Gamma camera images were acquired at 48 or 72 hours after injection, and assessed for antibody localization. Positive images were obtained in all five osteosarcomas and four other primary malignant sarcomas. Two of the four other primary bone tumors gave positive images. Three patients with trauma had negative images as did one patient with Paget's disease. Two pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1988
1988
1991
1991

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Many studies over the last 10 years have demonstrated that radiolabelled tumour associated antibodies may be successfully used for the imaging of a variety of human cancers including those of the colon (Chatal et al, 1984), ovary (Shepherd et al, 1987), breast (Rainsbury et al, 1983), lung (Chan et al, 1986), skin (Carrasquillo et al, 1987) and bone (Armitage et al, 1986). These studies have reported the results of imaging but have not attempted to correlate the results with the biodistribution of the radiolabelled antibody.…”
mentioning
confidence: 99%
“…Many studies over the last 10 years have demonstrated that radiolabelled tumour associated antibodies may be successfully used for the imaging of a variety of human cancers including those of the colon (Chatal et al, 1984), ovary (Shepherd et al, 1987), breast (Rainsbury et al, 1983), lung (Chan et al, 1986), skin (Carrasquillo et al, 1987) and bone (Armitage et al, 1986). These studies have reported the results of imaging but have not attempted to correlate the results with the biodistribution of the radiolabelled antibody.…”
mentioning
confidence: 99%